PENDIDIKAN KESEJAHTERAAN KELUARGA SEBAGAI BANGUNAN KARAKTER ANAK BANGSA - Asih Kuswardinah; Dyah Nurani Setyaningsih (Universitas Negeri Semarang, 2015)
Family Welfare Education as A Character Building of young generation. The long-term aim of this study is to implement PKK subject to all Students of Elementary Education in Indonesia. Major Target: 1. describing teacher’s attitude of PKK subject as an effort to build student’s character; 2. Describing level of validity for PKK textbook for Junior High School. According to its aim, this study is applied study; According to its method, this study employs RD design; while according to its explanation, this study is quantitative descriptive research. Population of this study is Junior High School teacher in Semarang Regency. Sample, art teacher of National-standardized Junior High School in Semarang. Data was collected through questionnaire and FGD. Data analysis is using descriptive percentage. The result of the study: 23% Junior High School teachers were strongly agree to the material of PKK subject. 85% teacher stated that PKK textbook is strongly relevant while 15% said that it is relevant. Conclusion: 1) the average number of Junior High School teachers in Semarang Regency were strongly agree to implement PKK Subject; 2) the average number of teachers in Semarang Regency stated that the material was strongly relevant to be implemented. Suggestion: a. Teachers are expected not only to teach skills but also teach the soft skills related to family welfare. b. It is also recommended for the Department of Education and Culture, especially in Elementary Education in Semarang Regency to arrange such policy about the significance of PKK subject for students.